Peran kepala TPQ Al hidayah, dalam membangun model pembaharuan lembaga pendidikan Al qur’an - fahani, maulfi fahrul; Ferdiansyah, Muhammad; Muttaqin, M.Imamul (Maliki Interdisciplinary Journal, 2025)
Effective leadership is very important in Al-Quran educational institutions, especially in schools. This study considers the role of the head of TPQ in building a renewal model for Al-Quran educational institutions. The research method used is observational qualitative research. The results of the study indicate that good leadership includes the ability to influence and inspire, have a clear vision, and master communication. In addition, the Head of TPQ is also responsible for developing teacher quality, creating a positive culture, managing change, and implementing institutions. Strong leadership has a positive impact on teacher motivation, educational innovation, and student performance. A proactive and integrated learning environment that allows for effective leadership encourages students to actively participate in learning and achieve their greatest potential. This study is expected to provide an active contribution to the development of TPQ as a quality informal Islamic educational institution and to attitudes towards time.